PENGARUH KEPUASAN DAN KEPERCAYAAN TERHADAP KOMITMEN DAN DAMPAKNYA TERHADAP LOYALITAS - Husein Umar (Business Management Journal, 2017)
The purpose of this survey is to examine the effect of satisfaction and trust to commitment and their impact to loyalty. The population includes everyone who travelling to Bandung from Jakarta by toll road suttle service Cipaganti and Xrans. There were 300 respondents purposively selected. Data analysis using Structural Equation Modelling produce the following results : 1) satisfaction influences commitment, 2) Trust influences commitment, 3) commitment influences loyalty, 4) Satisfaction influences loyalty, 5) Trust influences loyalty. Key Words- Trust, satisfaction, commitment, loyalty.